Ayer Hitam community participations in conservation: a conceptual paper - Azli, Aina farahin; Abas, Siti Aisah (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
Peat swamp forest (PSF) has high potential in delivering wide range of economic and social benefits through developing ecotourism to conservation. However it is rarely to be optimised due to poor performance and involvement of locals as they are been viewed to simply gain benefits from tourism development rather than having cooperation in the process of achieving such development. Therefore, this conceptual paper aimed to explore the concept of community participations to conserve peat swamp forest (PSF) in Ayer Hitam Johor. In such, local participation is vital to ensure the availability of natural resources are well managed purposely to maximise the benefits, minimise the cost and reduce negative impacts resulted from conservation. This conceptual paper is solely based on secondary data in which gathered from journal, articles, research project and manual.